2015
DOI: 10.1159/000430317
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Dependent Neuroprotective Effects of NaHS in Ischemia Brain Injury Involves the PARP/AIF Pathway

Abstract: Background/Aims: Stroke is among the top causes of death worldwide. Neuroprotective agents are thus considered as potentially powerful treatment of stroke. Methods: Using both HT22 cells and male Sprague-Dawley rats as in vitro and in vivo models, we investigated the effect of NaHS, an exogenous donor of H2S, on the focal cerebral ischemia-reperfusion (I/R) induced brain injury. Results: Administration of NaHS significantly decreased the brain infarcted area as compared to the I/R group in a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…Moreover, our results revealed that CELF1-induced apoptosis seems to be mediated via caspase-independent but AIF-dependent pathway. A number of studies have demonstrated that changes in AIF may cause DNA damage and lead to caspase-independent apoptosis, contributing to the development of various diseases [23, 24]. In this study, though it has been indicated that AIF is one of the downstream effectors of CELF1 mediating the apoptotic process, it is still not clear whether CELF1 can physically interact with AIF mRNA and posttranscriptionally regulate its expression or not.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, our results revealed that CELF1-induced apoptosis seems to be mediated via caspase-independent but AIF-dependent pathway. A number of studies have demonstrated that changes in AIF may cause DNA damage and lead to caspase-independent apoptosis, contributing to the development of various diseases [23, 24]. In this study, though it has been indicated that AIF is one of the downstream effectors of CELF1 mediating the apoptotic process, it is still not clear whether CELF1 can physically interact with AIF mRNA and posttranscriptionally regulate its expression or not.…”
Section: Discussionmentioning
confidence: 78%
“…H 2 S is produced naturally in mammalian tissues and exhibits various biological and physiological effects [14-17], such as modulated metabolic state [18], mitochondrial function, cellular redox status, and cell apoptosis [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Acting as a neuromodulator, H 2 S exerts anti-inflammatory, anti-apoptotic and antioxidant effects on the central nervous system [14-16]. In the central nervous system, cystathionine β-synthase (CBS) is abundantly expressed, which initiates the trans-sulfuration pathway catalysing the amino acid cysteine (Cys) to H 2 S [17].…”
Section: Introductionmentioning
confidence: 99%